“Black Esophagus” or Gurvits Syndrome: A Rare Complication of Diabetic Ketoacidosis - Vivek Choksi; Kairavee Dave; Rulz Cantave; Sameer Shaharyar; Jeevan Joseph; Uday Shankar; Steven Kaplan; Hamid Feiz (Case Reports in Gastrointestinal Medicine)
Acute esophageal necrosis (AEN) also known as “black esophagus” or necrotizing esophagitis is a rare syndrome characterized by a striking diffuse patchy or circumferential black appearance of the esophageal mucosa that preferentially affects the distal esophagus and terminates at the gastroesophageal junction. Only 88 patients over a span of 40 years have received this diagnosis, and the prevalence of this disease ranges from 0.001 to 0.2% of cases in literature. It more commonly affects men (4 : 1 ratio) in the sixth decade of life. It is associated with a high mortality rate, approaching 32%. We report a case of AEN presenting in the setting of diabetic ketoacidosis (DKA), affecting both the proximal and distal esophagus.